2006
DOI: 10.2753/mis0742-1222230207
|View full text |Cite
|
Sign up to set email alerts
|

When Online Reviews Meet Hyperdifferentiation: A Study of the Craft Beer Industry

Abstract: We analyze how online reviews are used to evaluate the effectiveness of product differentiation strategies based on the theories of hyperdifferentiation and resonance marketing. Hyperdifferentiation says that firms can now produce almost anything that appeals to consumers and they can manage the complexity of the increasingly diverse product portfolios that result. Resonance marketing says that informed consumers will purchase products that they actually truly want. When consumers become more informed, firms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
382
6
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 694 publications
(404 citation statements)
references
References 29 publications
12
382
6
4
Order By: Relevance
“…Herr et al (1991), Lee et al (2009), Xue andZhou (2010), Yang and Mai (2010), and Yin et al (2014) empirically show that negative WOM has a stronger impact than positive WOM. A second argument asserts a positivity effect (Clemons et al, 2006;East et al, 2007;Gershoff et al, 2003;Skowronski & Carlston, 1989). Gershoff et al (2003), Clemons et al (2006), and East et al (2007 show that positive reviews have a stronger impact than do negative ones.…”
Section: E-wom Valencementioning
confidence: 97%
See 1 more Smart Citation
“…Herr et al (1991), Lee et al (2009), Xue andZhou (2010), Yang and Mai (2010), and Yin et al (2014) empirically show that negative WOM has a stronger impact than positive WOM. A second argument asserts a positivity effect (Clemons et al, 2006;East et al, 2007;Gershoff et al, 2003;Skowronski & Carlston, 1989). Gershoff et al (2003), Clemons et al (2006), and East et al (2007 show that positive reviews have a stronger impact than do negative ones.…”
Section: E-wom Valencementioning
confidence: 97%
“…Three competing arguments have been proposed concerning this recommendation valence: the positivity effect (Clemons, Gao, & Hitt, 2006;East, Hammond, & Lomax, 2007;Gershoff, Mukherjee, & Mukhopadhyay, 2003;Skowronski & Carlston, 1989), negativity effect (Chiou & Cheng, 2003;Fiske, 1980;Skowronski & Carlston, 1989;Yin, Bond, & Zhang, 2014), and no effect (Cheung, Lee, & Rabjohn, 2008;Doh & Hwang, 2009). However, the research results have been mixed.…”
Section: Introductionmentioning
confidence: 97%
“…As a result, they negatively influence the number of shoppers interested in a product and the related conversion rate. Previous literature also shows the variance in ratings play a significant role in determining which new products grow fastest in the marketplace (Clemons et al 2006). Therefore we propose:…”
Section: Information Content Of Online Reviewsmentioning
confidence: 96%
“…Therefore it increases the conversion rate of a product. Previous studies showed that the mean of online product reviews had a significant effect on sales (e.g., Chevalier and Goolsbee 2003;Clemons et al 2006;Dellarocas et al 2007). And we expect that mean of online product reviews will have similar impact on conversion rate.…”
Section: Information Content Of Online Reviewsmentioning
confidence: 96%
See 1 more Smart Citation